Páli paradoxonok avagy „szolgálati” paradoxonok - Attila SZABÓ (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica, 2015)
Pauline Paradox or the “Service” Paradox. This paper investigates how Saul of Tarsus ,who is rather be known as the apostle Paul, is thinking and is teaching, about his office and service, which means to follow Jesus Christ. Meanwhile, – as he deals and applies with such things – it turns out that Paul was a connoisseur of classical Greek literature, acquainted with his contemporary philosophical thought, a brilliant mind, arguing with the Stoic and Epicurean philosophers in Athens – perhaps also due to the fact that Tarsus was a famous Greek education centre, and he was trained by that „school”. When – in the letter to Titus – quotes the so-called lie-paradox-one critic accuses Paul not only to present a logically false reasoning, but straight the lack of inspiration by the Holy Spirit. By examining Titus 1,12–13 and 2Corinthians 6,1–10, my aim is to prove that: Paul did not present a logically false reasoning, we are dealing with existential paradox, and why both passages are called – paradoxically – the paradox of service.